(untitled) (Journal of Agriculture and Plant Sciences, 2013)
An examination of the number of flowers on flowery branches and thepercantage of insemination of flowers on one line (H-100) was conducted,separated from a local population in the Strumica region, in correlation with thetemperature conditions in the year of examination.From the results (table 1) the following can be seen: the number offlowers formed on the flowery branches of the plant, is the lowest at the firstflowery branch (4.95). The number of flowers at the second branch is raising andreaches its maximum at the third flowery branch (7.55). Then, the number offlowers at the fourth and the following flowery branches decreases.The percantage of insemination by flowery branches, depends on theclimate conditions, which often have a negative influence on the fruit formationof the tomatoes grown in extreme conditions in which the maximum temperaturein May and June in the year 2002 reached 36.6ºC (June), and the minimalreached 6.6ºC in May, and 9.0ºC in June.The treatment of the flowers with tomatin (Ortomone EC), increases thepercentage of insemination at the first and the second flowery branch for about14%, while at the third and fourth flowery branch, the percantage ofinsemination is, to some extent, lower (3.0%).